BUDAYA ORGANISASI DAN KEPUASAN KERJA KARYAWAN PT. X MEDAN - Sherly Tarigan, Sutarto Wijono (Jurnal Cakrawala Ilmiah, 2023)
Organizational culture is one of the tools to help the development of employee empowerment and trust in management so that it is related to high job satisfaction and the amount of organizational commitment. This research aims to determine the relationship between Organizational Culture and Job Satisfaction of Employees of PT X Medan. The research method used in this research is quantitative method and uses saturation sampling technique. Thus, of all employee members of PT. X Medan, there were 40 employees who became samples in this research. Data collection in this research used measuring instruments of organizational culture scale developed by Robbins & Judge and job satisfaction scale compiled by Luthans. The results of data analysis found that there is a positive and significant relationship between organizational culture and employee job satisfaction. With a value of r = 0.805; <0.05 through the Pearson Product Moment test. In addition, there is an effective contribution of organizational culture to job satisfaction of 43%. Thus, the better the organizational culture implemented by the company, the higher the level of employee job satisfaction.